The good politician : folk theories, political interaction and the rise of anti-politics - Clarke, Nick; Jennings Will, Moss Jonathan, Stoker Gerry (New Delhi Cambridge University Press, 2018)
Surveys show a lack of trust in political actors and institutions across much of the democratic world. Populist politicians and parties attempt to capitalise on this political disaffection. Commentators worry about our current 'age of anti-politics'. Focusing on the United Kingdom, using responses to public opinion surveys alongside diaries and letters collected by Mass Observation, this book takes a long view of anti-politics going back to the 1940s. This historical perspective reveals how anti-politics has grown in scope and intensity over the last half-century. Such growth is explained by citizens' changing images of 'the good politician' and changing modes of political interaction between politicians and citizens. Current efforts to reform and improve democracy will benefit greatly from the new evidence and conceptual framework set out in this important study.
Includes bibliographical references and index.
Keywords: Political participation; Apathy